Collaborative care in eating disorders treatment: exploring the role of clinician distress, self-compassion, and compassion for others - Josie Geller; Avarna Fernandes; Allison C. Kelly; Lindsay Samson; Suja Srikameswaran (Journal of Eating Disorders, 2023)
Plain English Summary Collaborative care involves showing curiosity and concern for patients’ wellbeing regardless of their adherence to treatment, providing choices, and supporting the patient in deciding what is best for them. Although collaborative care has been shown to contribute to better treatment outcomes than directive care, it is common for clinicians to be directive, resulting in negative attitudes toward treatment and lower levels of adherence. A factor that may contribute to the care clinicians provide is their experience of distress and how they respond to their own and others’ distress in times of difficulty. In this study, self-compassion and compassion for others were associated with greater use of collaborative care, with compassion for others being the stronger predictor. Clinicians’ own experience of distress was not related to the manner in which they offered support. Fostering compassion in clinical environments could support the delivery of collaborative care.